Chemical composition of Artemisia annua L. leaves and antioxidant potential of extracts as a function of extraction solvents - Iqbal, Shahid; Younas, Umer; Chan, Kim Wei; Zia-Ul-Haq, Muhammad; Ismail, Maznah (MDPI, 2012)
This study was conducted to investigate the chemical and nutritional composition of Artemisia annua leaves in addition to determination of antioxidant potential of their extracts prepared in different solvents. Chemical composition was determined by quantifying fat, protein, carbohydrate, fiber, tocopherol, phytate, and tannin contents. Extraction of A. annua leaves, for antioxidant potential evaluation, was carried out using five solvents of different polarities, i.e., hexane, chloroform, ethyl acetate, methanol and water. Antioxidant potential was evaluated by estimating total phenolic (TPC), flavonoid (TFC) contents, ferric reducing antioxidant power (FRAP), Trolox equivalent antioxidant capacity (TEAC), DPPH radical scavenging activity and lipid peroxidation. Efficiency of different solvents was compared for the yield of antioxidant extracts from leaf samples and a clear variation was observed. The highest TPC, TFC, TEAC, DPPH radical scavenging and lowest lipid peroxidation were observed in MeOH extracts, whereas aqueous extract exhibited high ferric reducing antioxidant power; suggesting MeOH to be the most favorable extractant.